MATHEMATICS TEACHERSâ€™ ABILITIES IN DEVELOPING FORMATIVE ASSESSMENT AFTER THE INTRODUCTION OF LESSON STUDY AND OPEN APPROACH INNOVATIONS - Sampan Thinwiangthong; Colleen M. Eddy; Maitree Inprasitha (UUM Press, 2020)
Purpose â€" The main purpose of this study was to examine mathematics teachersâ€™ abilities in developing formative assessments when teaching algebraic reasoning after utilizing two innovations: lesson study and open approach.     Methodology â€" A single group quasi-experimental research design was employed in two mathematics classes in a school in Chaiyaphum province, Thailand. The target group was all the 11 mathematics teachers, who were pre-tested, then post-tested afterthe lesson study and open approach training. This was followed bytheir participation in setting up a lesson study group and conducting 10 lesson study cycles involving two research participants who were teaching two selected classes. The instruments were a questionnaire, the Assess Today rubric, interview protocols, 10 lesson plans, field notes, classroom observation video recordings, and studentsâ€™ written work. The AssessToday rubric was the main instrumentwritten work. The AssessToday rubric was the main instrumentused to determine the ability level of the mathematics teachers indeveloping formative assessment in terms of seven components,namely learning targets, question quality, nature of questioning, selfevaluation,observation of student affect, instructional adjustment,and evidence of learning.     Results â€" The pre-test and post-test results showed an improvementin the mathematics teachersâ€™ understanding about formativeassessment, the methods used in formative assessment, and how theycould use the data from the formative assessment while they wereimplementing the two innovations. In addition, the AssessToday rubric showed that both mathematics teachers were progressinggradually from novice, apprentice to practitioner level in theirabilities in developing formative assessment after the 10 cycles ofinnovation practices in all the seven components. The results implythat the mathematics teachers showed vast improvement in their abilities in developing formative assessment after they implemented the lesson study and open approach innovations in their teaching.     Significance â€" The results contribute significantly to knowledge about the usefulness of the lesson study and open approach innovations in enhancing mathematics teachersâ€™ abilities in developing formative assessment.